Educational Social Assistance and Human Capital Development: Evidence from Marginalized Students in Jakarta - Suputra, I Dewa Ayu Mytha Logenta Yanti; Eddyono, Fauziah (Yayasan Ilomata, 2025)
Socioeconomic disparities in Jakarta continue to hinder the development of high-quality human resources, particularly among marginalized communities. In response, the Jakarta Provincial Government introduced the Kartu Jakarta Mahasiswa Unggul (KJMU) program to improve access to higher education through targeted social assistance. This study investigates the effectiveness of KJMU by examining the influence of educational social assistance on recipients’ behavior, its impact on human capital quality, and the mediating role of behavior in that relationship. Utilizing the Theory of Planned Behavior, data were collected through a Likert-scale questionnaire from 155 KJMU recipients and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings indicate that social assistance has a significant positive effect on recipients’ behavior. However, neither educational assistance nor behavior showed a direct statistically significant impact on the quality of human capital, as measured by academic achievement, employability, and study efficiency. Among these indicators, academic performance exhibited the strongest association, while employment waiting time showed the weakest. These results suggest that while KJMU effectively fosters academic motivation and positive attitudes, it alone may be insufficient to enhance overall human capital quality. Complementary interventions such as career mentoring, soft skills training, and post-graduation support are recommended to strengthen the long-term outcomes of educational social assistance programs.